Consumers' susceptibility to interpersonal influence as a determining factor of ecologically conscious behaviour. Issue 1 (2014) - ,
<x xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine affect of consumer susceptibility to interpersonal influence (CSII) and demographics on ecologically conscious consumer behaviour (ECCB). Design/methodology/approach – Data were collected through mall intercept technique in six cities across India. Findings – ECCB and CSII scales were applicable in Indian context. Factor analysis revealed two factors for ECCB scale: ecologically conscious purchase behaviour and green product attitudes. Normative, informative influence of CSII and income were predictors to ecologically conscious purchase behaviour. Normative influence emerged as predictor to green attitudes. Research limitations/implications – The study focuses itself only on CSII factors. It does not examine influence of variables like personal values, risk perception, and personality on ECCB. It does not examine role of consumers' attitude towards conservation of energy and natural resources. Practical implications – The findings can be of immense use to firms marketing green brands in India. Social group acceptance and conformance is important for Indian consumers; advertising and promotional campaigns should use social groups for marketing green products. Consumer involvement and engagement can be created through social networking web sites. Ecologically concerns should be rewarded in order to encourage consumers to adopt green attitudes. Originality/value – Green marketing and ecologically conscious behaviour are upcoming research areas in India. There is limited research to understand Indian consumers' concerns about environment. ECCB and CSII scales were used as it was assumed that using scales which have been tested and validated in other cultures would give reliable results. <ack> <x xml:space="preserve">Acknowledgements</x> The author wants to extend her gratitude towards the editor and the anonymous reviewers' for their indispensable and valuable suggestions and comments that improved the quality of the paper significantly. </ack>